2008
DOI: 10.1007/s00384-008-0603-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality–morbidity after emergency–urgent colorectal surgery

Abstract: The main risk factors for postoperative morbidity and mortality following emergency colorectal surgery are related to: (1) patients' ASA score, (2) colonic ischemia, and (3) perioperative bleeding. These variables should be considered in the elaboration of future scoring systems to predict outcome of emergency colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 26 publications
9
34
1
2
Order By: Relevance
“…Four patients were surgically treated with success, and one died. These results compare favorably to the outcomes after emergent colectomy in general (mortality, 14 %; morbidity, 36 %) [25] and specifically for LGIB with a mortality rate that can be as high as 27 % [8].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Four patients were surgically treated with success, and one died. These results compare favorably to the outcomes after emergent colectomy in general (mortality, 14 %; morbidity, 36 %) [25] and specifically for LGIB with a mortality rate that can be as high as 27 % [8].…”
Section: Discussionmentioning
confidence: 68%
“…In the literature, Lipof et al [13] reported 15 % of recurrences of hemorrhage (8 patients out of 71) with a mean follow-up of 32 months. Tan et al [25] reported 13 % of rebleeding at 30 days or more after the first episode (4 of 32 patients). These data finally confirm the safety of the procedure, even after long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Mandava et al (5) reported this rate to be 12% while Bielecki (15) reported a rate of 16.9%. Factors affecting mortality are advanced age, ASA score > 3, stoma creation, blood transfusions, technique of anastomosis, presence of colonic ischemia, advanced tumor stage and metastatic disease (16)(17)(18). In our series mortality rate was 29.4 % (n=10).…”
Section: Discussionmentioning
confidence: 54%
“…The incidence of AL is a polyethyologic problem and depends on the location and conditions of its imposition. Multi-central investigations reveal that not only local changes in the bowel have an impact on AL, but also such factors as: blood transfusion, ASA score > 3, smoking, alcohol abuse, patients with diabetes mellitus, hypertonic disease, hypoproteinemia, overweight, age, sex, tumor stage, the use of steroids and neoadjuvant chemoradiotherapy, heart and lung failure and many others [7][8][9][10][11][12][13][14][15]. AL increases the risk of local recurrence and reduces overall 5-year survival [16,17].…”
Section: Introductionmentioning
confidence: 99%